Comparison of Non-Surgical Methods for Treating Hemorrhoids: A Systemic Review - Miga-Orczykowska, Nadia; Lemieszek, Paulina; Sajkiewicz, Ilona; Rudnicka, Katarzyna (Quality in Sport, 2024)
Introduction and purpose Hemorrhoidal disease is one of the most common proctological problems worldwide. The etiology of hemorrhoidal disease has not been fully explained. Authors note that lifestyle factors and dietary habits are primarily responsible for hemorrhoidal disease. These include: a low-fiber diet, constipation, a sedentary lifestyle, and suboptimal body position during defecation commonly observed in Western societies. Due to the high prevalence of the disease in the population and the associated decrease in quality of life, outpatient procedural treatments that are highly effective and allow for a quick return to normal activity are very popular among patients. The aim of this study is to discuss non-surgical methods of hemorrhoid treatment. Material and methods This paper was based on a review of materials available on PubMed, searched using the following keywords: “hemorrhoids”, “sclerotherapy”, “rubber band ligation”, „infrared coagulation”, „laser hemorrhoidoplasty”, „Doppler guides hemorrhoidal artery ligation”. Results In recent years, there has been a significant development in non-surgical techniques for treating hemorrhoids, which are widely used in patients with grade I-III hemorrhoids and can be performed in an outpatient setting or during short hospital stays with the use of regional anesthesia, such as: Sclerotherapy, rubber band ligation, Infrared coagulation, Laser hemorrhoidoplasty, Doppler Guides Hemorrhoidal Artery Ligation. Conclusion In conclusion, non-surgical methods for the treatment of hemorrhoids offer a range of effective alternatives to conventional surgery. The choice of treatment should be individualized, taking into account the severity of the hemorrhoidal disease, patient preferences, and the potential for complications.